DEN NARRATIVE FIKTIONALITETS PRAGMATIK - Walsh, Richard (K&K - Kultur og Klasse, 2013)
THE PRAGMATICS OF NARRATIVE FICTIONALITY | “The Pragmatics of Narrative Fictionality” is chapter 1 of Richard Walsh’ book The Rhetoric of Fictionality. Narrative Theory and the Idea of Fiction. Columbus: Ohio State University, 2007.